2015
DOI: 10.1186/s12884-015-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy: knowledge and beliefs of medical practitioners in South Africa: a survey study

Abstract: BackgroundThere is compelling evidence for the benefits of regular exercise during pregnancy, and medical practitioners (MPs) can play an important role in changing antenatal health behaviours. The purpose of this study was to assess the knowledge, attitudes and beliefs of South African MPs towards exercise during pregnancy.MethodsA convenience sample of ninety-six MPs working in the private health care sector, including General Practitioners (n = 58), Obstetricians/Gynaecologists (n = 33) and other Specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
5
36
1
1
Order By: Relevance
“…We assume that the proven clinical benefits of exercise for mothers and their offspring are countered by a vague uneasiness about perceived possible risks. Many pregnant women express anxiety about exercising in pregnancy, mostly concerning the development of the unborn child, miscarriage and prematurity, injury and falls [35][36][37]. Currently available data, however, do not support these concerns for moderate exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the proven clinical benefits of exercise for mothers and their offspring are countered by a vague uneasiness about perceived possible risks. Many pregnant women express anxiety about exercising in pregnancy, mostly concerning the development of the unborn child, miscarriage and prematurity, injury and falls [35][36][37]. Currently available data, however, do not support these concerns for moderate exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our study supported the findings that increasing awareness could in fact be a facilitator for behaviour change, as women cited that they would more likely be active if they received information from their healthcare provider. A previous study by the author showed that as little as 19 % of South African medical practitioners provided information regarding physical activity during the prenatal visit [ 40 ]. Since pregnant women visit their healthcare provider on a regular basis, this may be an ideal opportunity to provide counselling and support that could improve physical activity levels [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies also report inadequate capacity of health personnel (43,51) . For example, in South Africa, only 19 % of health workers provide PA-related information during antenatal visits (69) .…”
Section: Physical Activity Behaviourmentioning
confidence: 99%